Neurofeedback treatment of children with attention deficit hyperactivity disorder - Pop-Jordanova, N; Markovska-Simoska, S; Zorcec, T (Македонска академија на науките и уметностите, Одделение за биолошки и медицински науки = Macedonian Academy of Sciences and Arts, Section of Biological and Medical Sciences, 2005)
Biofeedback is a modern computer-related technique used for assessment and therapy of many psychophysiological disorders, especially stress-related ones. After a short overview of the basic concepts of biofeedback, in this study the application of EEG biofeedback (neurofeedback) in the assessment of and therapy for attention deficit hyperactivity disorders (ADHD) is presented and discussed.